1998
DOI: 10.1002/macp.1998.021991024
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylate networks containing chiral calamitic liquid crystalline side groups

Abstract: A one-step copolymerization of ferroelectric methacrylate monomers leading to networks is presented. Oriented networks are obtained and electro-optical investigations are described. Smectic C* and another smectic phase are found in slightly crosslinked networks. For higher crosslinking densities, only the high temperature smectic C* phase was found. Electro-optical measurements were performed on the networks, and significant changes in the ferroelectrical properties were found. For crosslinking densities highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Mesogenic monomers containing two reactive groups, or prepolymers incorporating reactive groups, can be photo or thermally polymerized or crosslinked in one or two steps with the addition of a non-mesogenic crosslinking agent. At present, the backbone of side chain LCEs is based on polysiloxane [5][6][7][8][9], polyacrylate and polymethacrylate [10,11]; in addition, LCEs have been extended to slightly crosslinked main chain polymers and combined polymers [12,13]. The chemical composition of the LCEs, apart from the crosslinking unit, is similar.…”
Section: Introductionmentioning
confidence: 99%
“…Mesogenic monomers containing two reactive groups, or prepolymers incorporating reactive groups, can be photo or thermally polymerized or crosslinked in one or two steps with the addition of a non-mesogenic crosslinking agent. At present, the backbone of side chain LCEs is based on polysiloxane [5][6][7][8][9], polyacrylate and polymethacrylate [10,11]; in addition, LCEs have been extended to slightly crosslinked main chain polymers and combined polymers [12,13]. The chemical composition of the LCEs, apart from the crosslinking unit, is similar.…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore been necessary to synthesize various kinds of side‐chain cholesteric LCEs to explore their potential applications. However, to the best of our knowledge, for cholesteric LCEs previously reported, especially with polysiloxane as a backbone, the mesogenic crosslinking agent was little used 37–41…”
Section: Introductionmentioning
confidence: 99%
“…Mesogenic monomers containing two reactive groups, or prepolymers incorporating reactive groups, can be photo or thermally polymerized or crosslinked by one or two steps with the addition of a nonmesogenic crosslinking agent. At present, the backbone of side‐chain LCEs is based on polysiloxane,1, 5–9, 13–17 polyacrylate, and polymethacrylate 18–26. In addition, LCEs were also extended to slightly crosslinked main‐chain polymers and combined polymers 19, 27–30.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in a similar way, copolymerization with a nonmesogenic crosslinking agent leads to a downward shift in the clearing point as increasing proportions are added to liquid‐crystalline polymers. However, only a few articles reported that LCEs were synthesized with rigid rod‐like crosslinking agents (mesogenic or nonmesogenic) 5, 6, 17, 26…”
Section: Introductionmentioning
confidence: 99%